2017
DOI: 10.1111/ijpp.12338
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial utilization in an Iraqi province: a comprehensive evaluation of antibiotic source and cost

Abstract: The antibiotic consumption ratio in this province was comparable to neighbouring countries, but far higher compared to European countries. Penicillins, cephalosporins and quinolones were the most popular antibiotics. Around half of the antibiotics consumed were made by national pharmaceutical companies that mainly produce oral antibiotics. The public sector consumed a higher portion, but spent a lower amount compared to private sectors. This is the first time report of antibiotic consumption in Iraq. More stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
15
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 17 publications
1
15
1
1
Order By: Relevance
“…Those who purchased prescription only medications (POMs) without a prescription were satisfied because they did not have to visit the doctor. For example, a previous Iraqi study reported that community pharmacy patients can obtain antibiotics without prescription ( 25 ). On the other hand, those who purchased medications for others usually complained about the pharmacy service when it was good because they had to wait for pharmacist to prepare and dispense the medications…”
Section: Discussionmentioning
confidence: 99%
“…Those who purchased prescription only medications (POMs) without a prescription were satisfied because they did not have to visit the doctor. For example, a previous Iraqi study reported that community pharmacy patients can obtain antibiotics without prescription ( 25 ). On the other hand, those who purchased medications for others usually complained about the pharmacy service when it was good because they had to wait for pharmacist to prepare and dispense the medications…”
Section: Discussionmentioning
confidence: 99%
“…It disbursed more than 50% of the cost burden. 15 The preparation of IV medicines requires the use of an aseptic technique. The consumption of IV is rarely warranted.…”
Section: Discussionmentioning
confidence: 99%
“…7 Several studies showed that the different type of antibiotics consumed at ambulatory care services. [8][9][10][11][12][13][14][15] Each country had different antibiotics and policy antibiotics prescribing guidelines. In Saudi Arabia, there is no national surveillance system of antimicrobial drug consumptions.…”
Section: Introductionmentioning
confidence: 99%
“…( 6 10 ) Analgesics, cough and cold preparations, and laxatives are the most common abused medications in Middle East countries. ( 11 , 12 ) In Iraq, lacking official enforcing of prescription necessity and absence of auditing on pharmacy-kept prescriptions may explain patient access to most of medication types without prescription in community pharmacies. In most circumstances (except for controlled substances), Iraqi patients can keep doctor prescriptions after receiving POMs from community pharmacies to use it for refilling with or without doctor permission.…”
Section: Introductionmentioning
confidence: 99%